Effectiveness of red betel leaf extract (piper crocatum) as a disinfectant based on removable dentures of thermoplastic nylon material: Efektivitas ekstrak daun sirih merah (piper crocatum) sebagai disinfektan basis gigi tiruan lepasan bahan nilon termoplastik - Sapitri, Kadek Dwi Dessy; Sugianitri, Ni Kadek; Annutama (Makassar Dental Journal PDGI Makassar, 2025)
Safe and effective natural alternative materials are needed, one of which is red betel leaf extract (Piper crocatum) or RBL which contains many active compounds that have antifungal effects. This study discusses the effectiveness of 10% and 20% concen-trations of RBL extract on the growth of Candida albicans colonies on thermoplastic nylon bases. A pure laboratory experimental study with a post-test only control group design was conducted using 9 samples of 1x1x0.2 cm thermoplastic nylon base soaked in C.albicans suspension for 24 hours, then grouped by extract concentration and soaked for 6 hours. Samples were grown on sa-bouraud dextrose agar media and incubated at 37°C for 24 hours. The number of colonies was determined with a colony coun-ter and analysed with Kruskal-Wallis and Mann-Whitney tests. The average number of colonies in aquadest group was 126, the 10% extract group was 28 colonies, while the 20% extract group had no colonies. It was concluded that the 20% RBL extract was most effective in killing C.albicans colonies. This effectiveness is obtained from the work of bioactive compounds in RBL that damage the walls and metabolism of fungal cells. The contact duration of 6 hours provides optimal time for penetration of active compounds to the surface of the material.